Alternative metallurgical process for artisanal gold mining - Aramburú Rojas, Vidal (2011)
The study sample is a refractory ore with an average grade of 19.31 g/TM provided by artisanal miners in the area and Yanga from the province of Canta, Lima. The mineralogy of the sample showed the presence of the following minerals: Gold, Chalcopyrite, covellite, chalcocite, sphalerite, pyrite, arsenopyrite, magnetite, hematite, goethite, rutile and bargains as photos indicate 1, 2, 3, 4, 5 and 6. The minerals found in larger volumes are bargains, Pyrite and Chalcopyrite in photo 6 are interlaced with gold particles chalcopyrite and pyrite, with the larger size of 17 microns of gold. In the first phase were carried out metallurgical testing with the hub centrifugal Knelson with 5 kg of sample, gravitational force of 60 G’s and water pressure of 3 psi, for different particle sizes as 52.25%, 60.66%, 67.13% and 74.64% - 200 mesh. The metallurgical balances indicate that the best test is selected with a particle size of 67.13% - 200 mesh, yielding 300.20 g/TM of concentrate, 33.66 and 51.59% recovery of radio concentration (Table 3). In the second stage cyanidation tests were carried out of the Knelson concentrator tailings, for different particle sizes mentioned in the first stage cyanidation for 24 hours and 300 RPM agitation. Relatively the best evidence was obtained with a particle size of 74.64% - 200 mesh to obtain a gold recovery of 70.02% with 1.62 intake and 9.76 Kg/TM of cyanide and lime, respectively (Table 8) Regrind the Knelson concentrator tailings to a particle size of 87.25% - 200 mesh, increasing the time to 48 hours cyanidation and agitation at 500 RPM. The result is a gold recovery of 81.06% with consumption of 2.52 and 11.05 kg /TM of cyanide and lime, respectively (Table 9).